The Impact of Global Price Volatility, Transportation Costs, and Tax Schemes on the Profitability of Palm Oil Exporters in West Sumatra Province - Judijanto, Loso (Westscience Press, 2025)
This study explores the influence of global price volatility, transportation costs, and tax schemes on the profitability of palm oil exporters in West Sumatra Province. Using a quantitative approach, data were collected from 175 exporters through a structured questionnaire employing a 5-point Likert scale. The analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The results indicate that global price volatility has a significant negative effect on profits, emphasizing the sensitivity of palm oil exporters to international market fluctuations. Transportation costs also negatively impact profits, reflecting the high logistics burden and regional infrastructure challenges. Meanwhile, tax schemes show a significant effect—partially negative due to high fiscal burdens, but also reflecting the importance of tax incentives in mitigating operational pressures. These findings highlight the need for integrated policy reforms that stabilize commodity prices, improve logistical efficiency, and design supportive tax frameworks to enhance the competitiveness and profitability of palm oil exporters in the region.